Mitochondrial Quality Control Impairment Is a Hallmark of TDP-43G376D ALS Patient-Derived Fibroblasts - Giuseppe Petito; Maria Ventriglia; Victoria Stefania Del Fiore; Arianna Cuomo; Federica Cioffi; Francesco Manfrevola; Flora Guerra; Lucia Bertuccini; Giulia Ricci; Gilda Cobellis; Antonia Lanni; Cecilia Bucci; et al. (Antioxidants, 2026)
Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disorder strongly associated with mitochondrial dysfunction and impaired proteostasis. Mutations in TARDBP, encoding TAR DNA-binding protein 43 (TDP-43), contribute to disease pathogenesis through cytoplasmic mislocalization and aggregation. Among these, the ALS-linked TDP-43G376D mutation has been previously associated with oxidative stress, mitochondrial fragmentation, and impaired oxidative phosphorylation. Here, we investigated the impact of TDP-43G376D on Mitochondrial Quality Control (MQC) pathways using patient-derived dermal fibroblasts carrying the mutation at early and advanced disease stages, complemented by HEK293T and Neuro2a cellular models expressing mutant TDP-43. We show that TDP-43G376D impairs mitophagic flux, as evidenced by reduced delivery of damaged mitochondria to lysosomes. This was accompanied by pronounced disruption of mitochondrial cristae architecture and accumulation of mitochondrial DNA damage, indicating compromised mitochondrial genome integrity. Furthermore, TDP-43G376D induces sustained activation of the mitochondrial Unfolded Protein Response (UPRmt), consistent with persistent mitochondrial stress, while selectively impairing the sirtuin-dependent antioxidant branch. In parallel, activation of the Endoplasmic Reticulum UPR (UPRER) was observed, indicating a coordinated engagement of cellular stress pathways. Collectively, our findings identify coordinated alterations in multiple MQC pathways associated with TDP-43G376D rather than isolated mitochondrial defects, supporting further investigation of these pathways in larger and disease-relevant ALS models.